Cultural and personal values interact to predict divorce - Sari Mentser; Lilach Sagiv (Communications Psychology)
Abstract We investigate the role of values in motivating the dissolution of marriage. Drawing on comprehensive value frameworks, we study how cultural values explain cross-national variation in divorce, how personal values explain further variation within nations, and how the two value systems interact together. In three archival studies, including more than 100,000 participants from over 55 countries, we study attitudes toward divorce as well as actual divorce. We found that divorce was more justifiable and likely in nations emphasizing autonomy values, and among individuals ascribing importance to self-direction, stimulation, and hedonism values. Divorce was less justifiable and likely in nations emphasizing embeddedness values, and among individuals ascribing importance to tradition and conformity values. Overall, the impact of personal values was stronger the more the culture emphasizes autonomy (vs. embeddedness) values. Understanding the role of values in divorce may inform individuals as to the values they desire in their future spouses.